Prostatic Artery Embolization Is Safe and Effective for Medically Recalcitrant Radiation-Induced Prostatitis - Nainesh Parikh, MD, MBA; Edward Keshishian, MD; Ayushman Sharma, MD; Monica Roca, MD; Brandon Manley, MD; Michael Poch, MD; G. Daniel Grass, MD, PhD; Javier Torres-Roca, MD; David Boulware, MS, MBA; Peter Johnstone, MD; Michael Montejo, MD; Johnna Smith, ARNP; et al. (Advances in Radiation Oncology, 2020)
Purpose: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) represents 90% of all chronic prostatitis cases and may occur after radiation therapy (RT) for localized prostate cancer. Medical therapy is effective in approximately 50% of cases, with no therapy demonstrating consistent efficacy in refractory cases. Prostatic artery embolization (PAE) is effective in men with lower urinary tract symptoms and benign prostatic hyperplasia. We report clinical improvement after PAE in a case series of men with CP/CPPS after RT. Methods and Materials: Nine men (median age 72 years; range, 61-83 years) with CP/CPPS after RT for prostate cancer underwent PAE. Baseline International Prostate Symptom Score was recorded in 5 patients (median 23; range, 4-26), Chronic Prostatitis Symptom Index score in 6 patients (median 22.5; range, 6-34), and quality of life (QoL) score in 8 patients (median 5; range, 2-6). Median baseline prostate volume was 49 cm3 (range, 22-123 cm3). Patients were followed up at 6 and 12 weeks with QoL, International Prostate Symptom Score, and/or Chronic Prostatitis Symptom Index score and magnetic resonance imaging. Results: Technical success (ie, bilateral embolization) was achieved in 78% (n = 7) of patients with the other 2 patients having undergone unilateral embolization with no major complications. Clinical success was seen in 89% (n = 8) of patients and QoL improved in 78% (n = 7) during the follow-up period. Conclusion: CP/CPPS after RT for localized prostate cancer is a highly morbid condition, with medical therapy successful in only 50% of cases. PAE may be a successful therapy for medically recalcitrant CP/CPPS, and further studies are necessary to understand the best patient selection and scenario for PAE in the setting of CP/CPPS.